Pterygium Colli: A Narrative Review with a Comparative Study of Lateral Approach Techniques - Mehri Turki, Imen (Facial Plastic Surgery, 2024)
Pterygium colli or webbed neck is a congenital deformity mainly found in Turner syndrome. It appears as a bilateral triangular fold extending from the mastoid to the acromion with hairy skin abnormality. Structural variation of the fold, as described by Mehri Turki's webbed neck classification, implies appropriate surgical repair. Despite the availability of a range of surgical techniques, it remains difficult to choose the most suitable one. Thus, this report aims to compare the lateral approach techniques by selecting those providing the best results. A literature search using PubMed and Google Scholar Database identified lateral approach techniques for pterygium colli. A critical reading led us to select criteria for comparison, linked to procedures and results. Moreover, according to aesthetic results, surgical techniques were classified into three categories. A total 16 articles were published from 1937 to 2020 and enrolling 48 patients were selected. The neck contour was obtained with all procedures. However, scars were hidden at the posterior neck in only 10 reports. Otherwise, the posterior hairline was corrected in only 6 reports. According to these outcomes, a classification of surgical technique was made allowing their pragmatic assessment. An objective assessment of lateral approach techniques was realized to help surgeons choose the most convenient one. From this study, a classification arises, based on aesthetic results, distinguishing three groups of surgical techniques and allowing their comparison. Techniques belonging to Group 2, using cervical advancement flap, were the most suitable, mainly both techniques described by Reichenberger and Mehri Turki.
Keywords: webbed neck; pterygium colli; surgical technique; aesthetic; lateral approach